ANALISIS KESULITAN BELAJAR SISWA KELAS TINGGI PADA MUATAN IPA DI SEKOLAH DASAR - Dina Fitriana,; Laila Aska Fuadiyah,; Suri Gafriani,; Arita Marini, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to analyze the learning difficulties of high grade students in science content in elementary schools. In this study, researchers used a type of qualitative method with content analysis techniques (content analysis). This learning difficulty is the condition of students experiencing obstacles or disturbances in the learning process, the causes can come from students' internal and external factors. Internal factors include: student attitudes in learning, motivation, physical health, while external factors include: variation of teachers in teaching, infrastructure, family environment. One of the factors that influence the difficulties experienced by students is because students find it difficult to understand scientific or foreign language, so they do not understand the material